Optimizing Language Acquisition: Stragies Chalenges in Indonesia Languane Education - Iwan Rumalean; Everhard Markiano Solissa (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to identify and optimize effective strategies in Indonesian language learning, as well as to face challenges that often arise in the context of language education in Indonesia. The methods used were literature analysis and field studies, which involved direct observation and interviews with language teachers and students in several primary and secondary schools. The results of the study show that a learning approach that integrates technology and social interaction significantly improves students' language skills. In addition, the main challenges faced include limited facilities, lack of effective teacher training, and wide local dialect variability. Based on these findings, the study recommends several strategies that can be adopted by policymakers and education practitioners to improve the effectiveness of Indonesian language learning, including the development of more inclusive digital resources and more comprehensive teacher training programs. This research contributes to a better understanding of the dynamics of language education in Indonesia and offers practical guidance to improve the language acquisition process.